Death and the Textile Industry in Nigeria - Renne, Elisha (Taylor & Francis, 2021)
burying, cemeteries, chapter, children, city, closure, coalition, colonial, conclusion, consequences, construct, dead, death, deaths, deindustrialization, dilemmas, elisha, experiences, fall, families, hardship, health, hometowns, houses, industry, introduction, kaduna, ktl, ltd, new, nigeria, p, problems, regimes, renne, rise, textile, textiles, time, unpaid, widows', work, workers.